Low birth weight babies under village conditions: feeding pattern, growth and motor development - Sri Kardjati; J A Kusin; C de With; U H Renqvist (Paediatrica Indonesiana, 1991)
Feeding, growth and motor development of low birth weight babies (LBW) were assessed among infants born from September 1982 through December 1984 in 3 villages in Madura. Mean birth weight of Madurese infants ranged from 2850 - 2950 g and the incidence of LBW from 9.5 -12.2 %. A larger percentage of the very small LBW babies (birth weight 2.0 - 2.2 kg) received breastmilk as the sole food in the first 6 months. Yet, force-feeding was also practiced for LBW babies. Infants remained in their growth channel according to birth weight, however, relative to the NCHS centiles at birth, LBW infants grew better in the first 6 months than normal birth weight (NBW) infants. Growth deteriorated conspicuously in the second half of infancy, irrespective of birth weight. There was no difference in motor development between LBW and NBW infants. Once they had survived, LBW infants appeared to do as well as NBW under village conditions.